Стійкість підприємства: діалектика статики і динаміки - Кіндрацька, Г. І. (Видавництво Львівської політехніки, 2014)
Розглянуто один з відносно нових напрямів фінансового аналізу – дослідження стійкості функціонування і стійкості зростання підприємства з метою оцінювання і моделювання позитивної динаміки його розвитку. Досліджено сутність взаємопов’язаних понять “стійкість розвитку”, “стійкість зростання”, “ділова активність”, “темпи стійкості економічного зростання”. Обґрунтовано розуміння оптимальних співвідношень між загальними показниками діяльності підприємства. Проаналізовано основні методики та запропоновано алгоритм дослідження стійкості зростання підприємства. The paper considers one of the relatively new areas of financial analysis – the study of financial stability and sustainability of growth of the company to assess and modeling positive dynamics of development. It was established that the steady growth of the company – longterm growth, which is characterized by the same ratio between the main indicators, and steady growth rate – the rate of activities expansion while preserving the existing operational and financial strategies. The essence of interrelated concepts of “sustainability”, “growth stability”, “sustainability rate of economic growth”, “business activity” investigated. Substantiated understanding of the optimal ratio between the general indicators of the company activity. Research of dynamic development of mining machinery enterprises showed that the proportion of enterprises with optimal growth rates of capital income fromsales and profit is only 17.1%of total number of enterprises. The basic methodology for assessing the sustainability of company economic growth analyzed. Sustained economic growth, as an integral characteristic of the enterprise activities, is expedient to evaluate by system tempo indicators: volume of sales, net profitability of sales of products; capitalization of net income; asset turnover; financial dependence. Changing the quantitative value of factor indicators, the company achieves the optimal rate of growth volume of sales of products, while keeping the financial balance. The algorithm of the research of sustainability enterprises growth suggested.
Sustainability of the enterprise: dialectics statics and dynamics
Keywords: фінансова стійкість; стійкість зростання; темпи стійкості економічного зростання; sustainability; financial stability; the rate of sustainable growth